Indonesian Vocational Engagement (I-VOCATIE): A New Concept in Improving Teacher Competencies 4.0 - Idrianti, Yasinta; Sasmoko; Noerlina; Abd Wahid, Nur Husna (Journal of Technical Education and Training, 2020)
The industrial revolution 4.0 is an era in which the industry collaborates cyber technology and automation so that it demands adaptation and transformation in various fields, especially in the field of vocational education. The condition of vocational education disparities in Indonesia is very high. Teachers who are really involved and have competence in the vocational field are needed. That is, the teacher experiences a unified whole within himself between the profession, professionalism, self-capacity and work itself which shows the totality of work but not workaholics called the Indonesian Vocational Teacher Engagement (I-VOCATIE). There are two formulations of the problem, namely: (a) what is the tendency of the condition of vocational teacher engagement in Indonesia? and (b) what is the most powerful dimension determining the formation of vocational teacher engagement in Indonesia? The research design was deployed a surveying method using the Neuroresearch model. The Neuroresearch method is a research method developed by Sasmoko which is a mixed method which consists of three research phases, namely exploratory research, explanatory research and exploratory research. These three stages can be done at once and can also be done alone. In this paper, we only used two stages, there are exploratory research and explanatory research. It was based on multistage sampling technique, the total sample of 856 vocational teachers in 30 provinces in Indonesia were managed to be collected. Data collection techniques with a Likert scale questionnaire ranging from 1 to 5. The results of the study: (a) vocational teachers in Indonesia tend to have internalized teacher professional status and the profession has become an interesting thing teachers develop significantly at Î± <0.05, and (b ) Nation Character (Nat_Char_X4) is the most powerful dimension determining the formation of vocational teacher engagement in Indonesia (Voc_TeachE_Y). Increasing the teacher’s performance will improve the nation character of vocational teachers.